A comedian and an activist walk into a bar the serious role of comedy in social justice - Borum Chattoo, Caty; Feldman, Lauren, 1977- (Communication for social justice activism ;, 2020)
"The contemporary intersection of comedy and social justice is embodied in the voices of comedians who are saying something serious about the world they inhabit while they make us laugh. But it also resides in the actions of social justice advocates who embrace comedy's artistic ability to grab and hold attention, to persuade and mobilize, to focus a critical lens on injustice, to humanize, and to allow optimism into seemingly hopeless social problems. Through rich case studies, audience research, and interviews with comedians and social justice leaders and strategists, A Comedian and an Activist Walk into a Bar: The Serious Role of Comedy in Social Justice explains how comedy--both in the entertainment marketplace and leveraged as cultural strategy--can engage audiences with issues such as global poverty, climate change, immigration, and sexual assault, and how activists work with comedy to reach and empower publics in the networked, participatory digital media age"--Provided by publisher